Hubungan Sisa Makanan Pasien Berdasarkan Cita Rasa Makanan dan Penampilan Makanan di Rumah Sakit Umum Daerah Bangli - Budianingsih, Ni Nengah; Gumala, Ni Made Yuni; Tamam, Badrut (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2025)
According to the 2023 Nutrition Installation Report at Bangli Regional General Hospital, food waste from three meals per day showed staple food (rice/porridge) had 22.4% leftovers, animal-based side dishes 24.5%, plant-based side dishes 29.8%, and vegetables 31%. These results exceed the Minimum Service Standard, which specifies food waste should be ≤20%. The study aims to determine the